The Impact of Organizational Justice on Employee Performance: A Case Study of Cantonment Board Employee Peshawar Pakistan - YASIR KHAN; MUHAMMAD AMJAD; AYESHA IRAJ; OBAID ULLAH BASHIR (Journal of Business & Tourism, 2021)
This article examined the impact of Organization Justice on employees’ performance in cantonment board Peshawar. The study was conducted using 150 employees as a sample and applied stratified random sampling technique. Statistical techniques i.e reliability analysis, Factor analysis, correlation and Regression applied. The results were obtained using correlation regression to know the direction, association and impact of variables and the effects organization justice on employee’s performance. The results found that Organization Justice affects the employee’s performance positively Therefore it is suggested that CBP should exercise such justice in the organization which will inculcate more confidence in the employees. All the hypotheses developed for this study has been proved through the analysis of this research study